Development of ELISA and Lateral Flow Immunoassays for Ochratoxins (OTA and OTB) Detection Based on Monoclonal Antibody - Fadlalla, Mohamed Hassan; Ling, Sumei; Wang, Rongzhi; Li, Xiulan; Yuan, Jun; Xiao, Shiwei; Wang, Ke; Tang, Shuqin; Elsir, Hoyda; Wang, Shihua (Frontiers in Cellular and Infection Microbiology, 2020)
Ochratoxins were important secondary metabolites secreted by fungi, and OTA and OTB are mainly significant mycotoxin, having toxic effects on humans and animals. Therefore, it is important to establish a rapid, sensitive, and precise method for ochratoxins detection and quantification in real samples. In this study, a stable monoclonal antibody (mAb) that recognizing both OTA and OTB toxins was employed for the establishment of indirect competitive ELISA (ic-ELISA), colloidal gold nanoparticles (CGNs), and nanoflowers gold strips (AuNFs) for detection of ochratoxins in real samples. A 6E5 hybridoma cell line stable secreting mAb against both OTA and OTB toxins was obtained by fusion of splenocytes with myeloma SP2/0 cells. The 6E5 mAb had a high affinity (3.7 × 108 L/mol) to OTA, and also showed similar binding activity to OTB. The optimized ic-ELISA resulted in a linear range of 0.06–0.6 ng/mL for ochratoxins (OTA and OTB) detection. The IC50 was 0.2 ng/mL and the limit of detection (LOD) was 0.03 ng/mL. The mean recovery rate from the spiked samples was 89.315 ± 2.257%, with a coefficient variation of 2.182%. The result from lateral flow immunoassays indicated that the LOD of CGNs and AuNFs were 5 and 1 μg/mL, respectively. All these results indicated that the developed ic-ELISA, CGNs, and AuNFs in this study could be used for the analysis of the residual of ochratoxins (OTA and OTB) in food and agricultural products.